Subsurface Modeling of High Sulfidation Epithermal Deposit Systems Based on Geomagnetic Data in the Tulungagung Area, East Java - Marisa, Sari; Dzil Mulki Heditama; Agata Vanessa; Y, Yatini (Pusat Survei Geologi, 2025)
The presence of metallic minerals in vuggy silica in Tulungagung, East Java, is characteristic of the high sulfidation epithermal (HSE) deposit system. This research quantitatively analyzes the distribution and geometry of metal mineral deposits in the research area using geomagnetic methods. The research analyzes the alteration and mineralization zones of the HSE deposits and builds a subsurface model. The geomagnetic method aims to determine subsurface conditions based on the magnetic properties of rocks. This research was conducted as many as 417 points with a distance between points of 50 - 700 meters, randomly from a lot area of 95 km2. The results of the reduce-to-pole (RTP) map analysis show that the alteration and mineralization zones of the HSE are seen in low magnetic anomaly values due to dominant alteration and the presence of complex faults, so that destructive magnetite occurs. The results of wave spectrum analysis obtained an estimated regional depth of ± 539 meters, which was used for subsurface modeling. The model shows the environment and geometry of the HSE deposits. The presence of alteration and mineralization in the study area is at low susceptibility values < 2 x 10-3 SI, controlled by faults and permeable lithologies. Dacite intrusions with high susceptibility values > 15 x 10-3 SI are interpreted as host rocks carrying mineralization in the study area.